No Effects of Anodal tDCS on Local GABA and Glx Levels in the Left Posterior Superior Temporal Gyrus - Dwyer, Gerard E.; Craven, Alexander R.; Hirnstein, Marco; Kompus, Kristiina; Assmus, Jörg; Ersland, Lars; Hugdahl, Kenneth; Grüner, Renate (Frontiers in Neurology, 2019)
A number of studies investigating the biological effects of transcranial direct current stimulation (tDCS) using magnetic resonance spectroscopy (MRS) have found that it may affect local levels of γ-aminobutyric acid (GABA), glutamate and glutamine, (typically measured together as “Glx” in spectroscopy) and N-acetyl aspartate (NAA). However, these effects depend largely on the stimulation parameters used and the cortical area targeted. Given that different cortical areas may respond to stimulation in different ways, the purpose of this experiment was to assess the as yet unexplored biological effects of tDCS in the posterior superior temporal gyrus (pSTG), an area that has attracted some attention as a potential target for the treatment of auditory-verbal hallucinations, auditory false perceptions and tinnitus. Biochemical changes were monitored using continuous, online MRS at 3 Tesla such that GABA and Glx levels could be measured before, during and after stimulation. Twenty healthy participants underwent a repeated-measures experiment in which they received both active anodal and sham intrascanner stimulation in a stratified, randomised, double-blind experiment. No significant changes in GABA, Glx or NAA levels were observed as a result of anodal stimulation, or between active and sham stimulation, suggesting that the pSTG may be less responsive to anodal tDCS than other cortical areas that have been similarly investigated.